From democratization to fostering resilience: EU intervention and the challenges of building institutions, social trust, and legitimacy in Bosnia and Herzegovina. Issue 7 (3rd October 2021) - Bargués, Pol; Morillas, Pol
ABSTRACT: Over the past two decades, the European Union (EU) has provided assistance and is unequivocally committed to the European perspective of Bosnia and Herzegovina (BiH). The EU strategy has evolved from a top-down approach to democratization and statebuilding in the 2000s towards a more pragmatic approach that seeks to foster resilience. However, BiH still suffers from internal party contestation and political paralysis, socio-economic challenges and areas of limited statehood. Thus, to what extent is the EU enhancing resilience? In this article we answer this question by examining how the EU is contributing to the three sources essential to obtain resilience, as understood by this Special Issue: efficient governance institutions, social trust, and the legitimacy of governance actors. By revising the EU support of BiH and interpreting to what extent it is contributing to these three sources, we conclude that the EU intervention in BiH is resulting in continuity – a process of slow progress that is increasingly perceived as frustrating for the local population – rather than peaceful change.